2021
DOI: 10.1016/j.shaw.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Workplace Experience of Caregiver-Employees: A Time-Series Analysis of a Workplace Intervention

Abstract: Background Rapid population aging in developed countries has resulted in the working-age population increasingly being tasked with the provision of informal care. Methods An educational intervention was delivered to 21 carer-employees employed at a Canadian University. Work role function, job security, schedule control, work–family conflict, familywork conflict, and supervisor and coworker support were measured as part of an aggregated workplace experience score. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Combining work and care is associated with several challenges that require adequate solutions for WKCs support [ 57 ]. Previous literature has described forms of carer support for WKC such as technology-based solutions and workplace measures [ 50 , 58 ]. However, little is known about how much carer support is provided to WKCs in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…Combining work and care is associated with several challenges that require adequate solutions for WKCs support [ 57 ]. Previous literature has described forms of carer support for WKC such as technology-based solutions and workplace measures [ 50 , 58 ]. However, little is known about how much carer support is provided to WKCs in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…The CSA Carer-Inclusive and Accommodating Organizations Standard ( B701-17 Carer-inclusive and accommodating organizations - CSA Group ) and accompanying handbook, Helping worker-carers in your organization ( B701HB-18 Helping worker-carers in your organization - CSA Group ) provide complimentary, ready resources to guide and inform this critical need. As suggested elsewhere ( Ireson et al, 2018 ; Ding et al, 2020 a; Ding et al, 2020 b; Williams et al, 2017 ; Lorenz et al, 2021 ; Ramesh et al, 2017 ; Wang et al, 2018 ; Sethi et al, 2017 ), large employers with the means necessary need to take a systemic approach to providing supportive work arrangements, such as non-contiguous paid and unpaid leave, flexible hours, and supportive technology for employees providing care. Finally, the social isolation of dependent care recipients also needs to be addressed and, if done, will help ease the growing responsibility of providing emotional support by CEs.…”
Section: Discussionmentioning
confidence: 99%
“…We theorize that this shift is largely a function of remote working mandates and burnout during COVID-19, increasing presenteeism rates. Our prior pilot study found that a similar workplace intervention was able to generate positive outcomes in work and health variables, such as family-supportive supervisor behaviour and self-reported health; however, absenteeism and presenteeism were unassessed in these studies [ 34 , 35 ]. Elsewhere in the literature, workplace interventions based on work–life policies in professional industries tend to produce increased productivity at an organizational level [ 36 ].…”
Section: Discussionmentioning
confidence: 99%